Implementasi Problem Based Learning Dalam Meningkatkan Kemampuan Pemecahan Masalah Siswa (Studi Kasus di SD Negeri Sukabumi Utara 07 Jakarta) - Prabowo, Indar; Purwanto , Anim; Muharam , Dudy Ruhyadi (LPPM Universitas Terbuka, 2024)
This research aims to determine the implementation of the Problem-Based Learning (PBL) approach at SD Negeri Sukabumi Utara 07 Jakarta, especially regarding students' abilities in solving problems. The research method used is a case study by collecting data through observation and interviews. The informants in this research were teachers and students. Research findings show (1) there is an increase in students' problem solving abilities after participating in PBL-based learning; (2) students are more involved and active in PBL learning; (3) students feel more motivated in the PBL learning process because they are faced with problems that are challenging and related to everyday life; and (4) PBL provides opportunities for students to develop social skills, such as teamwork, communication, and leadership, which are also very important in real life. This research makes an important contribution to strengthening results regarding the effectiveness of the PBL approach in improving students' problem-solving abilities at the elementary school level.